Dangerous Liaisons? - Norman L Jones (Canadian Respiratory Journal)
I sometimes feel that I am so dominated by circumstances and coincidences that I have little free choice, for example, when approaching an editorial. A case in point was a few days last month during which I attended a well-sponsored meeting of the Ontario Lung Association, reviewed a couple of papers reporting drug trials, read of the threats of litigation made by pharmaceutical companies to two Ontario researchers, heard of a public apology made by the New England Journal of Medicine regarding reviewers' conflicts of interest and received a critical letter from Dr Rob McFadden, an associate editor of the Canadian Respiratory Journal, about a sponsored publication that accompanied the last issue of 1999. All this I suppose reflects our rather ambivalent relationship with the pharmaceutical industry that supports many professional and academic programs but clearly expects some returns in addition to corporate tax benefits. We are now dependent on the industry's financial backing for academic and professional meetings that have become so large that they require large and expensive venues. But then the industry has the right to expect some return on its "investment" in such meetings.